The Trump century : how our president changed the course of history forever - Dobbs, Lou; Kneale, Dennis (Broadside Books, an imprint of HarperCollinsPublishers, 2020)
The Fox Business personality argues that Donald Trump has recreated the American economy and set the nation back on a path to prosperity through unconventional initiatives that will reverberate throughout the next century.